Statistical Indices of Land Use Changes and Nutrients Balance of Tomatoes and Peppers Production in Jordan Valley and Highlands (1999-2019) - Massimi, Mohunnad (Acta Geographica Debrecina Landscape & Environment series, 2021)
Climate change has caused pressure on water resources in Jordan. This was accompanied by the Syrian refugee crisis during the period 2009 to 2019. This descriptive study was conducted in the University of Debrecen, during the years 2020 and 2021 within the course of sustainable land use by collecting official statistical data from reliable sources in Jordan on the production of tomato, pepper, and paprika during five years 1999, 2004, 2009, 2014 and 2019 to compare the change in land use, crop sown structure, country production, unit area average yield and estimation of unit area pollution with major nutrients. The study showed an increased land used for the production of vegetables by (+ 37.84%) during the period from 2004 to 2014, high productivity per hectare for three crops from 2014 to 2019. Jordan had the highest tomato and paprika crop yields in 2014. The reason is due to the increase in the local and global demand for these crops along with other reasons, which have promoted the use of mass production agricultural techniques, the most important of which is chemical fertilization. Which caused the accumulation of phosphorus and potassium in soils.